Peran Hukum Perikatan dalam Penyelesaian Sengketa Perdata Studi Kasus PN Kuningan Putusan Nomor :3/Pdt.G/2024/PN Kng - Sri Mulyani; Wanda Asri SS; Wisnu Alwi Firdaus; Yogi Muhammad Iskandar Panambah; Zidni Octafia Hafsah (Letterlijk, 2024)
Engagement law plays a vital role in regulating legal relationships between parties involved in agreements in Indonesia. This article discusses how contract law functions as the main instrument in resolving civil disputes. The main focus of this research is on the mechanisms regulated by engagement law to resolve disputes arising from the implementation of agreements. Using a normative juridical approach, this article evaluates the principles of engagement law, types of engagement, and the dispute resolution procedures applied. Analysis of relevant civil cases in Indonesia provides a practical illustration of the application of contract law in the context of civil disputes. This article aims to provide comprehensive insight into the role of engagement law in achieving fair and efficient resolution in civil disputes and offers recommendations for improving the effectiveness of dispute resolution through engagement in the future.